FINANCIAL STATEMENT FRAUD DETECTION MENGGUNAKAN FRAUD HEXAGON THEORY PADA PERUSAHAAN DI JAKARTA ISLAMIC INDEX - Arsad, Muhammad; Amaroh, Siti; Cahya, Bayu Tri (JURNAL ILMIAH EDUNOMIKA, 2024)
The research aims to analyze indications of fraud by using the fraud hexagon in companies registered on the Jakarta Islamic Index (JII) for 2019-2021. The sample selection technique uses a purposive sampling technique, the number of research samples is 14 companies. The research uses analytical techniques using e-views tools. The results of the study prove that: (1) external pressure which is proxied has a significant effect on the detection of fraudulent financial statements; (2) financial stability has a significant effect on the detection of financial statement fraud; (3) financial targets have a significant effect on the detection of fraudulent financial reporting; (4) change of directors (DCHANGE) has no significant effect on the detection of fraudulent financial reporting; (5) ineffective monitoring has no significant effect on the detection of fraudulent financial reporting; (6) the nature of industry has a significant effect on the detection of fraudulent financial reporting; (7) change of auditor (AUDCHANGE) has no significant effect on the detection of fraudulent financial statements; (8) the frequent number of CEO's picture (CEOPICT) has a significant effect on the detection of financial statement fraud; and (9) collusion (COL) has no significant effect on the detection of financial statement fraud. Keywords: Fraud Hexagon, External Pressure, Financial Stability